2001
DOI: 10.1097/00000539-200108000-00017
|View full text |Cite
|
Sign up to set email alerts
|

The Differences in the Bispectral Index Between infants and Children During Emergence from Anesthesia After Circumcision Surgery

Abstract: In this study comparing the Bispectral index (BIS) in infants and children undergoing circumcision surgery by use of a standardized surgical and anesthetic technique, a significant decrease in BIS was detected in children during a stepwise decrease in end-tidal sevoflurane concentration. A similar relationship was not demonstrated in infants less than 1 yr old. In both children and infants, BIS increased significantly from pre- to postarousal. Additional studies are necessary to determine changes in BIS with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 12 publications
2
49
1
Order By: Relevance
“…In young children, it is possible that caudal analgesia does affect arousal, but BIS does not detect the change. In this respect, the findings of this study may be consistent with previous findings that have demonstrated poorer relationships between BIS and measures of anesthesia effect in small children (6,7). Secondly, the number of subjects enrolled in this study was small.…”
Section: Discussionsupporting
confidence: 92%
“…In young children, it is possible that caudal analgesia does affect arousal, but BIS does not detect the change. In this respect, the findings of this study may be consistent with previous findings that have demonstrated poorer relationships between BIS and measures of anesthesia effect in small children (6,7). Secondly, the number of subjects enrolled in this study was small.…”
Section: Discussionsupporting
confidence: 92%
“…Davidson et al . (14) studied BIS monitoring in infants and children receiving sevoflurane/N 2 O anesthesia with penile block for circumcision. The infants did not demonstrate the relationship between decreasing sevoflurane concentrations from 0.9% to 0.5% and rising BIS values at completion of surgery noted in the older children.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of age on BIS is still debated, with divergent findings reported in the anaesthesia literature [21,35]. Davidson and coworkers [35] compared BIS with the corresponding consciousness level during emergence from anaesthesia in a prospective, blinded manner in children (≥1 year old) and infants (<1 year old) undergoing elective circumcision. BIS increased significantly as sevoflurane concentrations decreased in children, but a similar relationship was not demonstrated in infants.…”
Section: Discussionmentioning
confidence: 99%